Seaweed nutraceuticals and their therapeutic role in disease prevention - Abirami R. Ganesan; Uma Tiwari; Gaurav Rajauria (Food Science and Human Wellness)
There is a growing interest that bioactive compounds from seaweed can play a major therapeutic role in disease prevention in humans. Seaweed bioactives including polysaccharides, pigments, fatty acids, polyphenols and peptides have been proven to possess various beneficial biological properties that could potentially contribute to functional food and nutraceutical development. These bioactive are explored for functional properties such as antioxidant, antibacterial, anticancer, antidiabetic, antitumor, antiviral, anti-inflammatory and anticoagulant properties, both in an in-vitro and in-vivo model system. This review critically examines the existing scientific knowledge on primary and secondary metabolites from seaweed and their functional properties for health-related conditions. It presents an update on the most recent evidence relating to their effect on health-related conditions and their action on cellular metabolism. Recent advancement and challenges for seaweed bioactive as a nutraceutical in relation to their biocompatibility and bioavailability to understand their therapeutic development is discussed. Keywords: Functional ingredients, Glucose metabolism, Lipid metabolism, Macroalgae, Bioavailability